Self-assessment of Students’ Life Quality in Latgales Region - Mietule, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The study of the scientific literature concerning the concept of quality of life makes it possible to draw conclusions on this concept positioning in different sub-sectors of science, the convergence with its concept of standard of living as well as various approaches to quality of life in quantitative and qualitative evaluation. The author entirely supports the scientific opinion, which emphasises the subjective evaluation of quality of life, i.e., quality of life is subjectively expressed in the form of individual's satisfaction with life in general. It consists of certain elements that are important to the individual or affect his quality of life. The aim of the research is to analyse the students' understanding and interpretation of the concept ‘quality of life’, as well as gather and interpret the respondents' subjective evaluation of quality of life. Students are the basis of this study. General elements characterising students’ quality of life are available education services, disposable income, health care, cultural and entertainment events, sense of ‘belonging’ to a family, acquaintances and friends. The author's initial assumptions regarding the fact that most respondents would express dissatisfaction with certain elements of quality of life and quality of life in general, were not confirmed by the study.